2021
DOI: 10.34012/jumkep.v6i1.1640
|View full text |Cite
|
Sign up to set email alerts
|

Terapi Birth Ball Untuk Menurunkan Intensitas Nyeri Persalinan

Abstract: Pain in childbirth has the highest degree of pain among other pain, so that many women are not ready to have children because they imagine the pain that will be presented at the time of labor later. The general objective of this study was to determine whether there was an effect of birth ball therapy on pain intensity in labor. Univariate and bivariate analysis using Wilcoxon test analysis. Bivariate analysis is used to see the effect of the independent variable (independent) on the dependent variable using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…(Widayani, 2016)Sugarman added that lavender aromatherapy has a refreshing aroma, which can relieve stress, reduce headaches and migraines, accelerate wound healing, and reduce pain levels. (Sagita, 2019). Kristanti (2015) explained that lavender molecules and particles, when inhaled, enter through the nose, are received by nerve receptors as a good signal, and are interpreted as a pleasant smell.…”
Section: Effect Of a Combination Of Endorphin Massage And Lavender Ar...mentioning
confidence: 99%
“…(Widayani, 2016)Sugarman added that lavender aromatherapy has a refreshing aroma, which can relieve stress, reduce headaches and migraines, accelerate wound healing, and reduce pain levels. (Sagita, 2019). Kristanti (2015) explained that lavender molecules and particles, when inhaled, enter through the nose, are received by nerve receptors as a good signal, and are interpreted as a pleasant smell.…”
Section: Effect Of a Combination Of Endorphin Massage And Lavender Ar...mentioning
confidence: 99%
“…Perez reported that the use of the birth ball is a useful tool for childbirth and pregnancy, and it has been used as a support tool in labor in recent years.6-8 The birth ball was rst used by midwives to accelerate the progress of labor and reduce pain during contractions [8,9]. It has been reported that the birth ball has bene ts such as decreasing the perception of labor pain, reducing the anxiety level, shortening the duration of the rst stage of labor, increasing the satisfaction of birth, and facilitating the descent of the fetal head [8,10]. In the studies, it has been suggested that the birth ball can be used actively to assist labor as it shortens the labor time and supports the pelvic oor muscles [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the birth ball has bene ts such as decreasing the perception of labor pain, reducing the anxiety level, shortening the duration of the rst stage of labor, increasing the satisfaction of birth, and facilitating the descent of the fetal head [8,10]. In the studies, it has been suggested that the birth ball can be used actively to assist labor as it shortens the labor time and supports the pelvic oor muscles [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to make various birth positions easier, various tools such as a birth ballorbirthchair can be used [7,[19][20][21]. In a previous study conducted to evaluate the effect of the birth ball on labor pain, pain levels felt by the pregnant women using the birth ball were found to be signi cantly lower than controls [10,11]. In a study conducted in primiparous pregnant women, it was concluded that the birth ball used in the rst stage of labor reduced the labor anxiety and labor pain [22].…”
Section: Introductionmentioning
confidence: 99%